C9orf72-related amyotrophic lateral sclerosis-frontotemporal dementia and links to the DNA damage response: a systematic review - Almalki, Seham; Salama, Mohamed; Taylor, Matthew J.; Ahmed, Zubair; Tuxworth, Richard I. (Frontiers in Molecular Neuroscience, 2025)
The G4C2 repeat expansion in C9orf72 is the most common genetic cause of amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD). While healthy individuals have fewer than 30 repeats, affected patients may carry hundreds to thousands. This expansion accounts for approximately 40% of familial ALS and 25% of familial FTD cases, and between 5 and 10% cases of sporadic ALS and FTD. Three overlapping pathological mechanisms have been proposed for the C9orf72 expansion: loss of function due to protein deficiency, gain of function through RNA foci, and the production of toxic dipeptide repeat proteins (DPRs) via repeat-associated non-ATG (RAN) translation. This systematic review investigates the role of DNA damage in C9orf72-related ALS-FTD. Analysis of twelve peer-reviewed studies showed that C9orf72 repeat expansions and DPRs compromise genome stability across four experimental models: human cell lines, induced pluripotent stem cell-derived neurons, rodent neurons, and postmortem tissue. We identified four mechanisms underlying DNA damage accumulation: disruption of the ATM pathway, impairment of DNA repair efficiency, formation of R-loops, and mitochondrial dysfunction with oxidative stress. In addition, several consequences of DNA damage were identified, including misrepair-mediated repeat expansion and activation of STING pathway. These findings highlight the key role of DNA damage in C9orf72-related pathology. Consistent with this, targeting DNA damage response factors extended lifespan and improved motor function in mouse models. This review highlights the contribution of DNA damage to C9orf72 pathology and suggest new therapeutic avenues, including personalized approaches based on genetic background.